Integrated solid waste management in megacities - M.A. Abdoli; M. Rezaee; H. Hasanian (Global Journal of Environmental Science and Management)
Rapid urbanization and industrialization, population growth and economic growth in developing countries make management of municipal solid waste more complex comparing with developed countries. Furthermore, the conventional municipal solid waste management approach often is reductionists, not tailored to handle complexity. Therefore, the need to a comprehensive and multi-disciplinary approach regarding the municipal solid waste management problems is increasing. The concept of integrated solid waste management is accepted for this aim all over the world. This paper analyzes the current situation as well as opportunities and challenges regarding municipal solid waste management in Isfahan according to the integrated solid waste management framework in six aspects: environmental, political/legal, institutional, socio-cultural, financial/economic, technical and performance aspects. Based on the results obtained in this analysis, the main suggestions for future integrated solid waste management of Isfahan are as i) promoting financial sustainability by taking the solid waste fee and reducing the expenses through the promoting source collection of recyclable materials, ii) improving compost quality and also marketing the compost products simultaneously, iii) promoting the private sector involvements throughout the municipal solid waste management system.